Pengaruh Beban Kerja Dan Budaya Organisasi Terhadap Kinerja Karyawan Teknik PT XYZ - Muhammad Andi Syahfarrel; Mochamad Vrans Romi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
From the results of the performance appraisal data obtained that there is a decrease in performance in Engineering Employees of PT XYZ. This study |aims to determine the effect of worklo|ad |and org|aniz|ation|al culture on the perform|ance of engineering employees both p|arti|ally |and simult|aneously. This type of rese|arch is qu|antit|ative with |a tot|al of 35 respondents for v|ari|ables X1 |and X2, n|amely engineering employees |and for v|ari|able Y is |a superior in the comp|any, then d|at|a collection techniques using libr|ary rese|arch |and field rese|arch, |and d|at|a |an|alysis techniques using descriptive |and |associ|ative methods with the SPSS version 26 progr|am |as |a d|at|a processing tool. The results of this study indic|ate th|at worklo|ad h|as |a positive effect on the perform|ance of engineering employees |and org|aniz|ation|al culture h|as |a positive effect on the perform|ance of engineering employees. Then worklo|ad |and org|aniz|ation|al culture simult|aneously |affect the perform|ance of engineering employees of PT XYZ.